Hypermanganesemia-Induced Cerebral Toxicity Mimicking an Acute Ischemic Stroke: A Case Report and Review of Overlapping Pathologies. (April 2021) - Reinert, Justin P.; Garner, Michael; Forbes, Laramie
Objective: To review and consider risk factors associated with the accumulation of and toxicity from manganese in patients receiving total parenteral nutrition (TPN).Case Summary: A 66-year-old female presented to the emergency department with right facial and arm weakness that initiated 1 hour prior to admission. Past medical history includes oral cancer with chronic aspiration and gastroparesis secondary to chemotherapy, TPN for 9 months, and a previous episode of right facial and arm parasthesias due to hypertensive emergency 4 years prior. The patient was assigned a National Institutes of Health Stroke Scale score of 6, cleared of an intracranial hemorrhage on imaging, and was administered tPA (tissue plasminogen activator) for an acute ischemic stroke after managing her hypertension to <185/110 mm Hg. Resolution of symptoms occurred within 24 hours. A magnetic resonance imaging of the patient's brain 24-hours post-tPA indicated an increased signal density in the globus pallidus, which in turn is linked with encephalopathy and has been described as a marker for hypermanganesemia.Discussion: Manganese is an essential trace element with a critical role in numerous physiologic functions. Though readily obtained from dietary sources and rarely causing issue, manganese provided to patients via TPN may result in toxicities. Though the presentation of neurotoxicities associated with TPN-delivered manganese has been previously documented, the clinical presentation of toxicity has never mimicked an acute ischemic stroke.Conclusion: Though an evaluation of overlapping pathologies is warranted, this patient's clinical presentation of manganese toxicity mimicked an acute ischemic stroke and resulted in the administration of a fibrinolytic. A more comprehensive appreciation of the implications of trace elements is demanded of clinicians.